Nuclear proteins TREF1 and TREF2 bind to the transcriptional control element of the transferrin receptor gene and appear to be associated as a heterodimer. - Roberts, M R (1989)
Two novel proteins that bind specifically to the transferrin receptor (TR) promoter, have been isolated from HeLa cell nuclear extract using a combination of ion exchange and oligonucleotide-affinity chromatography. TREF1 and TREF2, which have apparent molecular weights of 82 and 62 kDa, respectively, appear to be associated as a heterocomplex (TREF), and both proteins are able to contact target DNA directly. TREF interacts specifically with a region of the TR promoter which contains the TR transcriptional control element. This region is similar in sequence to the cAMP-responsive and phorbol ester-responsive elements found in several viral and cellular genes. Binding of TREF to the TR promoter results in modification of DNA topology over multiple helical turns, including a sequence revealed by a helical periodicity map as having an unusual structure.